Dinamika Stress Kerja Pada Karyawan Dinas Sosial Klaten - Viona Salsabella (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Work stress is a common phenomenon in various organizations and significantly impacts employee well-being and productivity. This study aims to understand the dynamics of work stress experienced by employees at the Social Services Department of Klaten, including its causes, effects, and management strategies. A qualitative descriptive method was used, with data collected through interviews and observations of five informants. The results indicate that the primary causes of work stress include ineffective communication, high workloads, limited human resources, and pressure from tight deadlines. The effects of work stress manifest in decreased productivity, physical and mental health issues, and strained social relationships. Employees adopt various coping strategies, such as seeking entertainment, isolating themselves, or relying on social support. The organization has implemented programs like capacity building, but additional policies are needed to enhance employee well-being. This study recommends improving communication, optimizing human resources, and implementing more effective stress management programs to create a healthier and more productive work environment.